OFFSHORE FLOATING MARINE FISH CAGE AQUACULTURE DEVELOPMENT PLANNING EVALUATION BASED ON HYDRO-OCEANOGRAPHY CONDITIONS IN SABANG BAY, WEH ISLAND - Ulung Jantama Wisha; Guntur Adhi Rahmawan; Koko Ondara; Wisnu Arya Gemilang; Ruzana Dhiauddin; Nia Naelul Hasanah Ridwan; . Ilham (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Sabang coastal bay becomes the area of significance where the development centered in the semi-enclosed area. Sabang Bay is well-known as the center of marine economy (Aquaculture, Harbor, and marine tourism). Recently, there is a planning initiated by Ministry of Marine Affairs and Fisheries (MMAF) to install the floating fish cage aquaculture (KJA) in the offshore area of Sabang Bay which the planning becomes a controversy between local people, local government, and researchers as well. This study aims to evaluate and discuss the impacts that will be happened if KJA is applied. Field surveys on hydro-oceanography aspects were done measuring currents, tides, waves, winds, bathymetry, water quality, as well as tourism condition. Based on those hydro-oceanography conditions, Sabang Bay categorized into calm water area where the sea current is weak (ranging from 0-0.12 m/s), whilst the high values of pH, salinity, and temperature are identified within the bay during low tidal condition. If KJA is installed within the bay, automatically it will pollute the water due to the accumulation of remaining fish feeder wastes. Moreover, within the bay, there are several attractive marine tourisms such as diving sites, the conservation area of Sophie Rickmers shipwreck site, and hot bubble (fumaroles hydrothermal vent). The presence of KJA will possibly disrupt marine tourism activities so that the implementation of KJA needs to be considered the impacts before installation.